Peran Tokoh Agama dalam Meningkatkan Kesadaran Moderasi Beragama Masyarakat Multikultural - Linda Dwi Novita Wardani (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
The country of Indonesia is famous for its multicultural society, which accepts and respects each other in all its forms including ethnicity, religion and nationality. Klepu Village is known as a harmonious village, which has a variety of religions including Islam, Catholicism and Protestant Christianity which have good relations and a high sense of tolerance between religions which plays an important role in religious moderation. This research aims to determine the role of religious figures in increasing awareness of religious moderation in multicultural communities in Klepu Sooko Ponorogo. This research uses a qualitative approach with a case study conducted in Klepu Village, Sooko, Ponorogo to explore relevant data and data collection techniques are carried out using observation, interviews and documentation. The results of the research conducted are (1) religious figures have a key role in increasing awareness, providing understanding and modeling religious moderation to the community (2) factors inhibiting religious moderation in Klepu Village come from internal and external factors. Internal factors include a lack of deep religious insight in society, fanaticism and a lack of awareness of tolerance, while external factors include inadequate human resources, the government not playing an active role in providing guidance regarding religious moderation and the influence of social media.